2015
DOI: 10.3389/fpsyg.2015.00113
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing perceptual and attentional skills requires common demands between the action video games and transfer tasks

Abstract: Despite increasing evidence that shows action video game play improves perceptual and cognitive skills, the mechanisms of transfer are not well-understood. In line with previous work, we suggest that transfer is dependent upon common demands between the game and transfer task. In the current study, participants played one of four action games with varying speed, visual, and attentional demands for 20 h. We examined whether training enhanced performance for attentional blink, selective attention, attending to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 37 publications
3
43
1
6
Order By: Relevance
“…Following Oei & Patterson (2013, 2015) who compared AVGP and NVGP visual capacity in this same task, we ran analyses on just the “2-targets 6-distractors” condition and just the “8-targets 0-distractors” condition as they did. Within the IMM group, AVGP did outperform NVGP on the “2-targets 6-distractors” condition (K AVGP: 1.650±0.118; NVGP: 1.346±0.113; one-sided t-test: t(25)=1.83, p=0.04) and on the “8-targets 0-distractors condition” (AVGP: 3.852±0.436; NVGP: 1.685±0.413; t(24.9)=3.6, p=7e-4), confirming enhanced visual memory in AVGP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Oei & Patterson (2013, 2015) who compared AVGP and NVGP visual capacity in this same task, we ran analyses on just the “2-targets 6-distractors” condition and just the “8-targets 0-distractors” condition as they did. Within the IMM group, AVGP did outperform NVGP on the “2-targets 6-distractors” condition (K AVGP: 1.650±0.118; NVGP: 1.346±0.113; one-sided t-test: t(25)=1.83, p=0.04) and on the “8-targets 0-distractors condition” (AVGP: 3.852±0.436; NVGP: 1.685±0.413; t(24.9)=3.6, p=7e-4), confirming enhanced visual memory in AVGP.…”
Section: Resultsmentioning
confidence: 99%
“…They measured the same 10 target/distractor-number conditions as Ophir and colleagues but reported only the “2-targets 6-distractors” (maximal number of distractors) and the “8-targets 0-distractors” conditions (maximal number of targets condition). Playing action video games, in comparison to other forms of video games, improved performance in both of these conditions suggesting that action video game experience improves both visual capacity and distractor suppression (see also, Oei & Patterson, 2015). …”
Section: Comparing Action Video Game Players To Media Multitaskersmentioning
confidence: 94%
“…They also show enhancements relative to NVGP performance in terms of the ability to flexibly distribute attention over space, 6,[44][45][46][47][48] monitor and track objects (i.e., both in foveal and peripheral vision), 6,31,44,46,49,50 and monitor and select information in time. 21,45,[51][52][53] Although researchers initially hypothesized that such differences may be the result of better attentional selection in early sensory processing, a series of electroencephalography studies have instead suggested that these behavioral differences are more likely the result of changes in "attentional control." Evidence in favor of this latter view includes both cross-sectional 54,55 and experimental 48 works showing that action gaming is associated with changes in parietal activity (yoked to attentional control), rather than occipital activity (yoked to early visual processing).…”
Section: The Influence Of Video Game Play On Cognition and Its Neuralmentioning
confidence: 99%
“…Therefore, the GE group may actually have benefited from the EVG to give better performance in the SKT. The same authors confirmed that the aforementioned transfer to a cognitive task is more likely if a common underlying ability is highly practiced in a video game during the same cognitive task (Oei, Patterson 2015).…”
Section: Discussionmentioning
confidence: 62%